2013
DOI: 10.3390/cryst3030431
|View full text |Cite
|
Sign up to set email alerts
|

Zintl Salts Ba2P7X (X = Cl, Br, and I): Synthesis, Crystal, and Electronic Structures

Abstract: Two barium phosphide halides, Ba 2 P 7 Br and Ba 2 P 7 I, were synthesized and structurally characterized by single crystal X-ray diffraction. Both compounds crystallize in the monoclinic space group P2 1 /m (No. 11) and are isostructural to Ba 2 P 7 Cl. The crystal structures of Ba 2 P 7 X (X = Cl, Br, I) feature the presence of heptaphosphanortricyclane P 7 3− clusters along with halogen anions and barium cations. According to the Zintl concept, Ba 2 P 7 X compounds are electron-balanced semiconductors. Quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Despite some deviations of the angles in the layered P 3 2− found in mP ‐BaP 3 from regular tetrahedral angles, no displacement of the ELF maxima from the line connecting atoms was observed. This is in contrast to the more strained isolated polyphosphide cage, P 7 3− , found in Ba 2 P 7 I in which ELF maxima are shifted from the edges of the base triangle 23. The observed ELF distribution allows for the qualification of both mS ‐BaP 3 and mP ‐BaP 3 as classical Zintl phases.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Despite some deviations of the angles in the layered P 3 2− found in mP ‐BaP 3 from regular tetrahedral angles, no displacement of the ELF maxima from the line connecting atoms was observed. This is in contrast to the more strained isolated polyphosphide cage, P 7 3− , found in Ba 2 P 7 I in which ELF maxima are shifted from the edges of the base triangle 23. The observed ELF distribution allows for the qualification of both mS ‐BaP 3 and mP ‐BaP 3 as classical Zintl phases.…”
Section: Resultsmentioning
confidence: 69%
“…We confirm that mS ‐BaP 3 can indeed be produced either from the reactions of elements at temperatures above 1150 K or by the use of small amounts of iodine as a transport agent. In the latter case, mS ‐BaP 3 formed at temperatures as low as 1073 K. However, iodine proved to be very reactive, and the reactions with more than a few crystals of I 2 led to the formation of Ba 2 P 7 I 23. To clarify the mS / mP phase relationship, we performed differential scanning calorimetry (DSC) characterizations of BaP 3 samples (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Polyphosphides are known to form a variety of crystalline structures with different elements [1][2][3]. The electronic structures of polyphosphides can be rationalized by the application of the Zintl concept [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In A 3 P 7 , (A = alkali metal) an electron is given from each atom A to allow the formation of the cage P −3 7 [1,6], in Ba 3 P 14 , three Ba atoms each give two electrons to allow the formation of two cages P −3 7 [7], in Ba 2 P 7 Cl Zintl salt, the total charge of two Ba +2 cations is compensated by a combination Cl − of and P −3 anions. Juli-Anna Dolyniuk and Kirill Kovnir [1] have shown that the Ba 2 P 7 Br and Ba 2 P 7 I isostructurally include the family of P −3 7 structures. A large number of Zint compounds have recently been synthesized and these structures offer abundant and interesting physical properties, such as semi-conductivity, superconductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation